2014
DOI: 10.1111/ajt.12798
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile Infection in Liver Transplant Recipients: A Retrospective Study of Rates, Risk Factors and Outcomes

Abstract: Clostridium difficile infection (CDI) occurs in 3-7% of liver transplant recipients (LTR). However, few data exist on the recent epidemiology, predictors and outcomes of CDI in LTR. A cohort study was performed including LTR from 2000 to 2010 at a tertiary care hospital in Detroit. CDI was defined as diarrhea with a stool C. difficile positive test. Data analyzed included demographics, comorbidities, length of stay (LOS), severity of CDI, rates of recurrence (<12 weeks), relapse (<4 weeks) and overall mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 19 publications
2
49
1
Order By: Relevance
“…However, one review [15] and several both nationwide and single-or multicenter studies have reported higher prevalence rates of CDI in hospitalized cirrhotics or LT recipients, and there is increasing recognition of these patients as a high-risk population for acquiring CDI [6][7][8][12][13][14][15][16]. Besides hospital-acquired CDI (when symptom onset takes place more than 48 h after admission to a hospital), community-acquired CDI (symptom onset occurs in the community or within 48 h of admission to a hospital) [17] has also been reported in cirrhotic patients [18].…”
Section: Epidemiologymentioning
confidence: 99%
See 3 more Smart Citations
“…However, one review [15] and several both nationwide and single-or multicenter studies have reported higher prevalence rates of CDI in hospitalized cirrhotics or LT recipients, and there is increasing recognition of these patients as a high-risk population for acquiring CDI [6][7][8][12][13][14][15][16]. Besides hospital-acquired CDI (when symptom onset takes place more than 48 h after admission to a hospital), community-acquired CDI (symptom onset occurs in the community or within 48 h of admission to a hospital) [17] has also been reported in cirrhotic patients [18].…”
Section: Epidemiologymentioning
confidence: 99%
“…Paralleling the increased incidence of CDI in the general population, there has been increased interest in CDI among patients with liver disease, particularly in those with liver cirrhosis and liver transplant (LT) recipients [6][7][8]. Patients with cirrhosis and LT are at particular risk for developing CDI because of their frequent and prolonged hospitalizations, antibiotic and PPIs use, multiple comorbidities, and immunosuppressant therapy [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…25 In addition to MDR infections, frequent antibiotic use and systemic immunosuppression facilitate frequent clostridium difficile (estimated at 3-7% incidence) after OLT. 26 …”
Section: Early Infectionsmentioning
confidence: 99%